Frankenstein - Sibley, Raymond; Amino, Monica Shelley, Mary Wollstonecraft (Ladybird Books London, 2015)
"Victor Frankenstein has always been fascinated by the darker side of nature. One fateful night, his sinister obsession triggers a chain of events that will have terrible consequences for Frankenstein and those closest to him."--Page [4] of cover